BIOGRAFI SULAIMAN AL-QANUNI: PENGUASA DINASTI TURKI UTSMANI PADA MASA KEJAYAAN - Sucipto - Sucipto (UIN Walisongo Semarang, 2022)
Abstract: This research aims at discussing the biography of Sultan Sulaiman al-Qanuni, starting from his childhood era until becoming the ruler of the Ottoman Turks. It is described in many literatures that Sulaiman's life is close to various sciences. Furthermore, in his youth he has shown a strong character as a leader. His skill in leading the Ottoman Empire made him a great Sultan who was respected and feared by his opponents. On the other hand, in the hands of Sulaiman al-Qanuni, the Ottoman Empire succeeded in achieving a golden age and glory. He was given the title al-Qanuni which means “the law maker”, which one of his contributions was the compiling of the law book used as a guide by the people of the Ottoman Empire. Sulaiman al-Qanuni's success can be seen in various fields, such as politics, economy, social, military, arts, and culture. This research focuses on literature research, using historical research methods, namely, heuristics, verification, interpretation, and historiography. Key Words: Biography, Sulaiman al-Qanuni, Ottoman Empire, Leadership Abstrak: Penelitian ini membahas tentang Sosok biografi Sultan Sulaiman al-Qanuni, dimulai sejak masa kecil hingga menjadi penguasa Turki Utsmani. Digambarkan kehidupan Sulaiman dekat dengan berbagai ilmu pengetahuan. Selanjutnya di masa mudanya ia sudah menunjukkan karakter yang kuat sebagai seorang pemimpin. Kepandaiannya dalam memimpin Imperium Turki Utsmani, menjadikannya seorang Sultan yang besar yang dihormati dan ditakuti oleh lawan-lawannya. Di sisi lain ditangan Sulaiman al-Qanuni Dinasti Turki Utsmani berhasil mencapai masa keemasan dan kejayaan. Dia digelari dengan gelar al-Qanuni yang berarti “pembuat Undang-Undang”, yaitu salah satu kontribusinya dalam menyusun kitab Undang-undang yang dijadikan panduan dan pegangan oleh masyarakat Dinasti Turki Utsmani. Keberhasilan Sulaiman al-Qanuni terlihat dalam berbagai bidang, seperti politik, ekonomi, sosial, militer, seni, dan budaya. Penelitian ini fokus pada penelitian pustaka, dengan menggunakan metode penelitian sejarah, yaitu, heuristik, verifikasi, interpretasi, dan historiografi. Kata kunci: Biografi, Sulaiman al-Qanuni, Turki Utsmani, Kepemiminan.